A genome-wide association study of kynurenic acid in cerebrospinal fluid: implications for psychosis and cognitive impairment in bipolar disorder - Sellgren, CM (Mol Psychiatry, 2013)
Elevated cerebrospinal fluid (CSF) levels of the glia-derived N-methyl-D-aspartic acid receptor antagonist kynurenic acid (KYNA) have consistently been implicated in schizophrenia and bipolar disorder. Here, we conducted a genome-wide association study based on CSF KYNA in bipolar disorder and found support for an association with a common variant within 1p21.3. After replication in an independent cohort, we linked this genetic variant—associated with reduced SNX7 expression—to positive psychotic symptoms and executive function deficits in bipolar disorder. A series of post-mortem brain tissue and in vitro experiments suggested SNX7 downregulation to result in a caspase-8-driven activation of interleukin-1β and a subsequent induction of the brain kynurenine pathway. The current study demonstrates the potential of using biomarkers in genetic studies of psychiatric disorders, and may help to identify novel drug targets in bipolar disorder.